Good Corporate Governance Dan Financial Distress Pada Perusahaan Manufaktur Di Indonesia - Ninda Febriyanti, Fahira; Khalifaturofi'ah, Sholikha Oktavi (Jurnal Ekonomi, 2023)
Good Corporate Governance is important for companies to overcome financial difficulties. This study intends to analyze good corporate governance and its influence on predicting the condition of companies in financial distress. Good corporate governance is proxied by institutional ownership, managerial ownership, directors, the board of commissioners, and the audit committee. By using logistic regression for 21 manufacturing companies from 2015 to 2019, it was found that the board of directors and audit committee had a negative effect on financial distress. The board of commissioners has a positive effect on financial distress. The other variables, namely institutional and managerial ownership, have no effect on financial distress. To avoid financial distress in manufacturing companies, it is necessary to have a large board of directors and an audit committee, but not a board of commissioners. The fewer the boards of commissioners, the easier it will be for companies to control financial conditions to avoid financial distress.